MANAGEMENT OF ENTERPRISE’S FINANCIAL SUSTAINABILITY AND IMPROVEMENT OF ITS METHODS (World Bulletin of Management and Law, 2024)
The article is dedicated to the solution of the relevant issue, concerning management of enterprise`s financial sustainability. Financial sustainability assessment is one of the most important principles of enterprise`s activity, which provides information about financial capabilities of the company at the time of its evaluation and for the future. It is a requirement for the enterprise activity, which provides a high level of competitiveness, efficiency and intensity. Thus, the restoration and strengthening of financial sustainability is a priority task for the enterprise, a basic precondition for its effective functioning.